Pengaruh Pencahayaan Alami Terhadap Kenyamanan Visual Pengguna Studi Kasus: Bening Coffee & Space - Azhar Ramy Ibrahim; Diana Susilowati (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2023)
Light is an important element in human life. Without lighting, humans cannot see an object visually. It is from the reflection of the light of these objects that humans visualize shapes clearly and see comfortably. The coffee shop as a public space certainly requires adequate lighting so that visual comfort is maintained. Visual comfort will be achieved if the terms and conditions for achieving visual comfort have been fulfilled, including the brightness level according to the recommended standards and the distribution of lighting according to the spatial layout according to the standards. With the aim to determine the natural and artificial lighting conditions in coffee shops and lighting standards for visual comfort, this study will use a comparative research method. Where this method compares lighting standards with research results. The results of this research are that the level of light intensity found outside and inside the building meets the SNI standard at 250 lux by taking data that has an average lux during the day and lux in the afternoon. The conclusion from this study is that BENING coffee & space on one of the visual comfort factors has met the visual comfort standards set by the SNI.